Age at detection and age at presentation of childhood cataract at a tertiary facility in Ibadan, Southwest Nigeria (2020)
Background: To describe factors which influence the age at detection and age at presentation of patients with childhood cataract at a tertiary eye care facility in Southwest Nigeria. Methods: A retrospective review of children who presented with cataract between 2011 and 2015. Case notes were reviewed and data on age at detection and presentation as well as other clinical information was collected and analyzed using Stata 12 statistical software. Results: A total of 164 cases were reviewed, 52.4% of them were boys. Median age at presentation was 48 months while the median age at detection was 13.5 months. Seventy-four (45.1%) children had congenital cataract, 31.1% had developmental cataract, and 21.3% had traumatic cataract. The child’s mother detected the cataract in 116 (70.7%) of the patients. Median age at presentation for patients with congenital cataract was 18 months and 84 months for developmental cataract. The median age at presentation for congenital cataracts that were noticed by the mother was 17 months compared with 72 months for those noticed by other caregivers (p = 0.0085). The median age at presentation for developmental cataracts that were noticed by the mother was 72 months compared with 114 months for those noticed by other caregivers (p = 0.0065). Gender of the child did not significantly influence the age at detection or presentation. The source of referral and the location of domicile did not significantly affect the time interval between detection of the cataract and presentation to hospital. Conclusion: The average age of children presenting with cataracts in our setting is older than in high income countries. Detection of the cataract by the mother increases the likelihood of early presentation; thus, focused maternal education may promote earlier detection and presentation. Keywords: Childhood, Cataract surgery, Access, Nigeria, Sub-Saharan Africa